(untitled) (Research, Society and Development, 2022)
This article seeks to present a review of the literature, referring to the evaluation of sports policies, specifically linked to high performance. This refers to a larger research that seeks to identify the logical model of the Bolsa-Atleta Program, in order to consider the possibilities for evaluating such a policy. For this reason, the search was focused on high performance sport. The search was carried out in the Scopus database, Academic Google and websites of Brazilian scientific journals. The terms used were “process evaluation sports policy” and “evidence based evaluation sports policy”. Respectively, 119 and 65 texts were found. Based on the reading of the abstracts, 25 articles corresponding to each term were selected, totaling a research corpus of 50 articles. Among these, titles that pointed to the reflection on evaluation in the sport of inclusion and/or participation, without specifically dealing with high-performance sport, remained. Thus, the abstracts were read again, which further reduced the aforementioned corpus. Extracting the repetitions of texts that appeared in the search for both terms, six articles were selected, for “evidence based evaluation sports policy”, and nine, for “process evaluation sports policy” – totaling 15 articles, which were read in full. In this sense, it is possible to infer that there is little production about the evaluation of sports policies, in a general sense, and even more in terms of high performance sport.